HIP JOINT FORMATION AFTER FUNCTIONAL TREATMENT OF CONGENITAL HIP DISLOCATION IN INFANTS - Akhtamov A.A. (Western European Studies, 2024)
In order to predict the formation of hip joints after bloodless treatment of congenital hip dislocation, X-ray data of 102 hip joints in 51 children were studied. The follow-up period is from 3 to 4 years. The results of the study showed favorable development of hip joints in 70.6% of children, with delayed formation of hip joints in 17.6% of children, unfavorable formation of hip joints in 11.8% of patients. With the growth of children after 2 years of age, the deterioration of the acetabular angle and the angle of pathological antetorsion is the main factor in the unfavorable formation of the hip joint after functional treatment.
Keywords: children; congenital hip dislocation; functional treatment